Epicatechin gallate and epigallocatechin gallate are potent inhibitors of human arylacetamide deacetylase. (August 2021) - Yasuda, Kaori; Watanabe, Kazuki; Fukami, Tatsuki; Nakashima, Shimon; Ikushiro, Shin-ichi; Nakajima, Miki; Sakaki, Toshiyuki
Abstract: Recently, in addition to carboxylesterases (CESs), we found that arylacetamide deacetylase (AADAC) plays an important role in the metabolism of some clinical drugs. In this study, we screened for food-related natural compounds that could specifically inhibit human AADAC, CES1, or CES2. AADAC, CES1, and CES2 activities in human liver microsomes were measured using phenacetin, fenofibrate, and procaine as specific substrates, respectively. In total, 43 natural compounds were screened for their inhibitory effects on each of these enzymes. Curcumin and quercetin showed strong inhibitory effects against all three enzymes, whereas epicatechin, epicatechin gallate (ECg), and epigallocatechin gallate (EGCg) specifically inhibited AADAC. In particular, ECg and EGCg showed strong inhibitory effects on AADAC (IC50 values: 3.0 ± 0.5 and 2.2 ± 0.2 μM, respectively). ECg and EGCg also strongly inhibited AADAC-mediated rifampicin hydrolase activity in human liver microsomes with IC50 values of 2.2 ± 1.4 and 1.7 ± 0.4 μM, respectively, whereas it weakly inhibited p -nitrophenyl acetate hydrolase activity, which is catalyzed by AADAC, CES1, and CES2. Our results indicate that ECg and EGCg are potent inhibitors of AADAC. Graphical abstract: Epicatechin gallate (ECg) and epigallocatechin gallate (EGCg) are strong inhibitors of the human arylacetamide deacetylase (AADAC). Image 1